Mechanical properties and morphological characteristics of polypropylene ternary nanocomposite (PP-LS-MWCNT) for industrial applications - Salawudeen, T. Olalekan; Muyibi, Suleyman Aremu; Yusof, Faridah; Mujidat O., Aremu (International Institute for Science Technology Education, 2013)
Polymer nanocomposites are credited with better properties compared with the conventional composite made from microfillers and have found potential applications in civil constructions and fabrication of process vessels. Dispersion of multiple fillers in polymer matrix has become a subject of interest as it addresses most of the common shortcomings observed in the binary composite and enhances the development of composites with multifunctional properties. Polypropylene (PP) ternary nanocomposites of layered silicate (LS) and multiwall carbon nanotubes (MWCNT) have been prepared at a pre-determined percentage (3%) layered silicate while the MWCNT loadings were varied between 0.1 and 0.7%. The investigation focused on the effect of MWCNT loadings on the binary precursor (PP/LS) measured in terms of tensile strength and Young’s modulus. The degree of enhancement was compared with the level of dispersion measured by wide angle X-ray diffraction (WXRD) and complemented with the morphological characterization using transmission and scanning electron microscope (TEM and SEM) respectively. The results show that the Sample 1 with 0.17% MWCNT displayed highest enhancement of 52.30MPa and 1759.32MPa for tensile strength and elastic modulus respectively compared with Sample 2 and 3 with higher MWCNT content that gave 48.19 and 1679.26MPa and 47.43 and 1726.14MPa for tensile strength and Young’s modulus respectively. WXRD gave up to 28Å and 20.11Å in the clay layer distance within the composite and LS respectively, indicating intercalation in the composite system. TEM images show clearly well distributed fillers in Sample 1 with 0.17% MWCNT, partly distributed in Sample 2 with 0.45% and array of network of carbon nanotubes in Sample 3 with 0.16% MWCNT. These results were complemented with SEM images which show that the composites developed are combination of exfoliation, intercalation and some micromixing. Key words: Polypropylene ternary Nanocomposites layered silicate (LS) multiwall carbon nanotubes (PP-LSMWCNT), tensile properties, morphological characterization,